Students’ perceptions of local wisdom integration in science learning in West Kalimantan and Sarawak - Lia Angraeni; Ira Nofita Sari; Kamalawati binti Dolhan; Chua Sim Huat (Universitas PGRI Pontianak, 2025)
This study investigates secondary school students’ perceptions of local wisdom integration in science learning in two border regions, West Kalimantan, Indonesia, and Sarawak, Malaysia. The study is grounded in culturally responsive teaching theory and constructivist learning principles, which emphasize the importance of contextual relevance in meaningful knowledge construction. A comparative quantitative research design was employed using a cross-sectional survey approach. A total of 100 students participated in the study, equally distributed between the two regions. Data were collected using a validated Likert-scale questionnaire measuring three perception dimensions: perceived relevance, perceived engagement, and perceived conceptual support. Descriptive analysis indicates that students in both regions demonstrate positive perceptions toward the integration of local wisdom in science learning. The highest mean scores were observed in perceived conceptual support, suggesting that students believe contextualized cultural content enhances their understanding of scientific concepts. An independent samples t-test reveals a statistically significant difference between the two regions; however, the effect size is small, indicating similar perception patterns overall. The findings suggest that integrating local wisdom into science instruction strengthens students’ engagement and conceptual clarity while maintaining scientific rigor. The study contributes empirical evidence to culturally responsive science education in Southeast Asian cross-border contexts and highlights the importance of contextual curriculum design. Implications for curriculum development, teacher training, and sustainability-oriented science education are discussed.